2010
DOI: 10.1007/s00134-010-1775-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of particulate contaminations of infusion solutions in a pediatric intensive care unit

Abstract: PurposeTo examine the physical properties and chemical composition of particles captured by in-line microfilters in critically ill children, and to investigate the inflammatory and cytotoxic effects of particles on endothelial cells (HUVEC) and macrophages in vitro.MethodsProspective, observational study of microfilters following their use in the pediatric intensive care unit. In vitro model utilizing cytokine assays to investigate the effects of particles on human endothelial cells and murine macrophages.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 18 publications
1
63
0
3
Order By: Relevance
“…When using filters during drug infusion, drug particles are captured by the filter membrane and can be analysed by electronic microscopy. In the study by Jack et al [66], microscopic analysis showed particles of approximatively 40 × 20 µm in size. In another study performed by Foinard et al [7], particles trapped by the filter membrane were also analysed, with a particle size of about 30 × 30 µm.…”
Section: Drug Incompatibilities: a Problem In Clinical Practicementioning
confidence: 94%
See 2 more Smart Citations
“…When using filters during drug infusion, drug particles are captured by the filter membrane and can be analysed by electronic microscopy. In the study by Jack et al [66], microscopic analysis showed particles of approximatively 40 × 20 µm in size. In another study performed by Foinard et al [7], particles trapped by the filter membrane were also analysed, with a particle size of about 30 × 30 µm.…”
Section: Drug Incompatibilities: a Problem In Clinical Practicementioning
confidence: 94%
“…Particles diffuse to the lungs through the venous system because of the increasing size of veins. Jack et al [66] showed that most particles have mean sizes within the range of 5 to 50 µm resulting in considerable particulate retention in the pulmonary capillaries of particles ranging from 5-10 µm in diameter. All particles smaller than the diameter of pulmonary capillaries pass through the lungs and diffuse into the different organs, including the liver and spleen, where particles can be phagocytised by the reticuloendothelial system.…”
Section: Route Of Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include phlebitis (3, 10 -13), pulmonary emboli (14 -16), pulmonary granulomas (3,11,17), immune system dysfunction (3,18), pulmonary dysfunction (13,15), infarction (15,19), and death (14, 20 -22). The patient risk associated with the injection of drugs containing particulate matter depends on a number of factors, including the route of administration used, the particle size and shape, the number of particles injected, the particle composition, and the patient population.…”
Section: Clinical Effects Of Injected Particulate Mattermentioning
confidence: 99%
“…Estimates are that patients in intensive care receive more than a million injected particles Ͼ2 microns in size daily (18,30,31). One method for controlling the particle load administered to critically ill patients has been through the use of final filters.…”
Section: Numbermentioning
confidence: 99%